2018
DOI: 10.3389/fpsyg.2018.00962
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Technology in Positive Psychology: Methodological Advances in the Science of Well-Being

Abstract: Advances in biotechnology and information technology are poised to transform well-being research. This article reviews the technologies that we predict will have the most impact on both measurement and intervention in the field of positive psychology over the next decade. These technologies include: psychopharmacology, non-invasive brain stimulation, virtual reality environments, and big-data methods for large-scale multivariate analysis. Some particularly relevant potential costs and benefits to individual an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…Although our findings add to the psychological underpinnings of conspiracist worldviews (Wood & Douglas, 2015), and to the emerging field of computational psycholinguistics (Sterling et al, 2020;Sylwester & Purver, 2015;Yaden et al, 2018), our research is not without limitations. First, while examining tweets from the top influential conspiracy and science influencers (and their online following) ensures greater ecological validity (Douglas et al, 2019), we cannot make causal inferences based on these data.…”
Section: Discussionmentioning
confidence: 83%
“…Although our findings add to the psychological underpinnings of conspiracist worldviews (Wood & Douglas, 2015), and to the emerging field of computational psycholinguistics (Sterling et al, 2020;Sylwester & Purver, 2015;Yaden et al, 2018), our research is not without limitations. First, while examining tweets from the top influential conspiracy and science influencers (and their online following) ensures greater ecological validity (Douglas et al, 2019), we cannot make causal inferences based on these data.…”
Section: Discussionmentioning
confidence: 83%
“…New technologies are changing several aspects of everyday life, and the speed with which they are implemented and integrated make technology-related impacts an area of particular scientific interest. Numerous studies have shown that new technologies can have very important therapeutic, rehabilitation, educational, and recreational implications (Costa, Cuzzocrea, & Nuzzaci, 2014;Griffiths, Kuss, & Ortiz de Gortari, 2017;Krutka, Nowell, & Whitlock, 2017;Yaden, Eichstaedt, & Medaglia, 2018), but other research has indicated that excessive use of technological devices can be risky, especially for some age groups, such as adolescents (Eleuteri, Saladino, & Verrastro, 2017;Kuss, & Griffiths, 2012). In fact, younger generations are increasingly using mobile phones, social media, gaming, and the Internet (Allen, Ryan, Gray, Mclnerney, & Waters, 2014;Griffiths, 2010), and without adequate regulation skills (Roberts, & Pirog, 2013), the availability and portability of new devices can make an over-use more likely, possibly with the end result of developing a form of technological addiction (Echeburua & de Corral, 2010;Griffiths, 1995;Kuss, & Billieux, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Through the use of new computational methods, researchers can utilize large amounts of data readily available online (Yaden et al, 2018). For instance, language data derived from social media can be analyzed with natural language processing tools such as Linguistic Inquiry and Word Count (LIWC;Pennebaker et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Both fields rely heavily on self-report measures (Yaden et al, 2018;see Hill et al, Chapter 7, this volume, for a review), which enable the efficient measurement of multiple dimensions of complex constructs. However, self-reports can be subject to self-presentation bias, especially when measuring socially desirable constructs (Tourangeau & Yan, 2007) such as religiousness (Presser & Stinson, 1998) and well-being (Heintzelman et al, 2015).…”
Section: Self-reportsmentioning
confidence: 99%